PENGARUH LIKUIDITAS DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Hotma Mentalita (LPPM STIKes SITI HAJAR dan Insight Power, 2022)
- The purpose of this study was to examine: (1) The Effect of Liquidity on Financial Performance, (2) The Effect of Firm Size on Financial Performance. This type of research is quantitative. The population used in this study are all textile and garment companies listed on the Indonesia Stock Exchange (BEI) 2018-9021. While the sample to be tested is in accordance with the research criteria that have been determined and the sampling technique is purposive sampling, and there are 10 companies that meet the sampling criteria. The secondary data collection method used is documentation. The analytical methods used for this research are: Panel data regression test, classical assumption test, goodness of fit test, and hypothesis testing. This research tested using panel data regression with Eviews 10. The results of this study indicate that liquidity has a positive and insignificant effect on financial performance, and company size has a negative and significant effect on financial performance. Keywords: liquidity, company size, and financial performance.